Turkey's Kurdish question from an educational perspective - İnce, Adem (Lexington Books, 2018)
Turkey's Kurdish Question from an Educational Perspective represents a comprehensive examination of all major factors in education--teachers, curriculum, policy documents, educational attainments and textbooks--that might possibly affect Kurds. It sheds a critical spotlight on the educational side of the issue, offering a summary of existing challenges, ways to deal with these problems, and the proposal of long-term solutions to achieve permanent peace in the region.